NF-κB Inhibition after Cecal Ligation and Puncture Reduces Sepsis-Associated Lung Injury without Altering Bacterial Host Defense. (18th November 2013) - Li, Hui; Han, Wei; Polosukhin, Vasilly; Yull, Fiona E.; Segal, Brahm H.; Xie, Can-Mao; Blackwell, Timothy S.
Abstract : Introduction . Since the NF-κ B pathway regulates both inflammation and host defense, it is uncertain whether interventions targeting NF-κ B would be beneficial in sepsis. Based on the kinetics of the innate immune response, we postulated that selective NF-κ B inhibition during a defined time period after the onset of sepsis would reduce acute lung injury without compromising bacterial host defense. Methods . Mice underwent cecal ligation and puncture (CLP). An NF-κ B inhibitor, BMS-345541 (50 µg/g mice), was administered by peroral gavage beginning 2 hours after CLP and repeated at 6 hour intervals for 2 additional doses. Results . Mice treated with BMS-345541 after CLP showed reduced neutrophilic alveolitis and lower levels of KC in bronchoalveolar lavage fluid compared to mice treated with CLP+vehicle. In addition, mice treated with CLP+BMS had minimal histological evidence of lung injury and normal wet-dry ratios, indicating protection from acute lung injury. Treatment with the NF-κ B inhibitor did not affect the ability of cultured macrophages to phagocytose bacteria and did not alter bacterial colony counts in blood, lung tissue, or peritoneal fluid at 24 hours after CLP. While BMS-345541 treatment did not alter mortality after CLP, our results showed a trend towards improved survival. Conclusion . Transiently blocking NF-κ B activity after the onset of CLP-induced sepsis can effectively reduce acute lung injury in mice without compromising bacterial host defense or survival after CLP.